Cell proliferation in the amputated limb of lizard leading to scarring is reduced compared to the regenerating tail. (11th March 2016) - Alibardi, Lorenzo
Abstract: After amputation, the tail of lizards regenerates while the limb forms a short scarring outgrowth. Using phospho‐histone‐H3 immunohistochemistry the mitotic activity of limb tissues at 12–25 days after amputation has been studied, when a limb outgrowth of 0.5–2 mm in length is covered by wound epidermis and the underlying connective is turning into a dense scar. In comparison with a regenerating tail of 3–5 mm in length, the number of dividing cells is reduced of 40–70% in different tissues of the scarring limb 1–2 mm in length at 18 days postamputation. Dividing cells are still present at 12–25 days postamputation in the cartilaginous epiphyses of the transected tibia and fibula and of the untransected femur. Also, the injured muscles present at the base of the scarring outgrowth still contain sparse dividing cells after 25 days postamputation of the limb. Together previous studies, the present observations suggest that after the initial proliferation of fibroblasts deriving from the injured tissues, especially from the dermis and intermuscle connectives during the initial 7–15 days postinjury, these cells cover the injured tissues underneath the wound epidermis, but rapidly produce high levels of collagen turning the initial blastema into a scar.